Freshwater conservation planning in the context of nature needs half and protected area dynamism in Bhutan. (November 2020) - Dorji, Tshering; Linke, Simon; Sheldon, Fran
Abstract: The conservation movement "Nature Needs Half" (NNH) aims to protect 50% of the earth by 2050. But increase in total protected area (PA) coverage alone does not guarantee adequate species protection, and identifying conservation priority areas that meet specific species conservation targets is suggested as a way forward. Further, PAs are dynamic entities and the loss event termed protected area downgrading, downsizing and degazettement (PADDD) can hamper efficacy of PAs in biodiversity conservation. Considering known threats to both biodiversity and PAs during systematic conservation planning can help identify robust conservation priority areas. Bhutan, a country that already achieved the NNH target through terrestrial-focused PAs and with hydropower as main cause of PADDD, provides a unique case study. We identify freshwater priority areas for Bhutan using Marxan, a widely used systematic conservation planning tool. We assessed two different Marxan scenarios: scenario 1 did not exclude planning units with hydropower sites during planning and scenario 2 excluded them. We found using freshwater species and forest types as conservation features during conservation planning afforded better protection to the species and forest types by the reserves over that by the existing PA system, though the reserves and existing PA system had similar total area. Further, the reserve from the scenario 2 provided similar protection to the freshwater species and forest types as to that provided by the reserve from scenario 1. Our findings suggest need to consider target species and known threats during conservation planning stage to better protect biodiversity even within NNH paradigm.